VERTEBRAL BODY RECONSTRUCTION FOR THORACOLUMBAR SPINAL METASTASIS - A REVIEW OF TECHNIQUES - Riaz, Salman; Fox, Richard; Lavoie, Michael V; Mahood, James K. (Journal of Ayub Medical College Abbottabad, 2006)
The spine is the most common site of skeletal metastases with its involvement occurring in up to 40% of patients. Metastatic spinal involvement can cause a number of sequelae like pain, instability and neurologic compression. About 10% of patients with involvement of the vertebral column will subsequently develop neurologic compression.The metastatic spinal lesions mostly affect the vertebral body and pedicle (85%). Management of spinal metastases remains controversial. Recent reports attest to the beneficial role of surgery. The role of decompressive laminectomy without stabilization, has been questioned. The Involvement of Vertebral Body and anterior compression had led to an increasing attention to anterior decompressive procedures, reconstruction and Stabilization. We Review here the Techniques described in literature for anterior reconstruction after vertebral corpectomy. Key Words: Spinal Metastasis, Vertebral Body, Laminectomy, Bone cement, Titanium Cages, Reconstruction.